HUMAN VALUES, HEALTH CONCEPTS, AND TREATMENT APPROACHES ARE CULTURE-DEPENDENT: WHY WESTERN PSYCHOLOGY DOES NOT SUFFICE - Walter Renner; Ingrid Salem (European Scientific Journal, ESJ, 2014)
We challenged the assumption that traditional Western psychology would possess worldwide validity. (1) We compared human values in European individualist vs. Arab and South African collectivist societies. E.g., whereas European religiosity (N = 456 Austrians) was regarded a private matter, in Arab culture (N = 737, American University, Cairo) being religious implied endorsing national Arabism and in South African, indigenous culture, for N = 400 respondents at Sovenga religiousness were intertwined with pro-social attitudes. Recently we confirmed theoretical predictions regarding differences in N = 336 Indian vs. N = 163 Central European respondents' style of moral judgment. – (2) In line with expectations, Diagnostic Criteria as set forth by DSM-IV-TR only insufficiently reflected the post-traumatic symptomatology in N = 150 refugees from Chechnya, Afghanistan, and West Africa and we found distinct differences with respect to symptomatology between these cultural groups. – (3) We tested a cultural self-help group (SHG) program for Chechen refugees in a randomized, controlled trial (N = 94). SHGs facilitated by Chechnyan laypeople were equally effective as Cognitive Behavior Therapy (CBT) and highly superior to the wait-list condition (Cohen's d = 0.93). – (4) We could not, however, replicate these findings with N = 66 female Turkish migrants with recurrent depression: neither SHG nor CBT reduced clinical symptoms. Western psychological paradigms must be replaced by culturally specific ones, but SHG only in some cases can replace treatment. Alternatively, culturally specific treatment approaches conducted by a clinical psychologist with a migration background is being studied in an Austrian psychosomatic clinic.